1992
DOI: 10.1021/ma00044a045
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of polyelectrolyte networks induced by their interaction with oppositely charged surfactants

Abstract: The interaction of charged surfactants with oppositely charged polyelectrolyte networks has been investigated. The effective absorption of the surfactant ions by charged gel is observed. The surfactantnetwork complex formation results in gel collapse. The influence of charge density and mobility, ionic strength, and network topology on complex formation has been studied. It has been shown that the surfactant ions in charged gel form micelle-like aggregates. Due to this fact the surfactant-network complexes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(163 citation statements)
references
References 3 publications
8
155
0
Order By: Relevance
“…The SDS-watergel interactions are dependent on the hydrophilic character of the network structure as well as of the surfactant properties. This SDS behaviour is well established in charged gels [32][33][34]. In fact, the charged swollen polymer gels form stable complexes with oppositely charged surfactants [34,35].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The SDS-watergel interactions are dependent on the hydrophilic character of the network structure as well as of the surfactant properties. This SDS behaviour is well established in charged gels [32][33][34]. In fact, the charged swollen polymer gels form stable complexes with oppositely charged surfactants [34,35].…”
Section: Discussionmentioning
confidence: 67%
“…This SDS behaviour is well established in charged gels [32][33][34]. In fact, the charged swollen polymer gels form stable complexes with oppositely charged surfactants [34,35]. The formation of such complexes results in aggregation of the surfactant ions at concentrations below the cmc in solution [36].…”
Section: Discussionmentioning
confidence: 75%
“…The extensive theoretical and experimental [138][139][140][141][142][143][144][145] studies have shown that the addition of anionic, cationic, and nonionic surfactants to the solution containing a gel can also influence the T V and swelling degree of hydrogels depending on their hydrophobicity and charge of the polymer network. In general, addition of anionic or cationic surfactant to the solution of nonionic hydrogel increases T V as well as the swelling range, whereas the nonionic surfactant does not affect T V or volume change.…”
Section: Surfactants As Effectors Of Hydrogel Volume Changementioning
confidence: 99%
“…After immersion of polyelectrolyte gel in the solution of the oppositely charged surfactants due to exchange reaction and hydrophobic interactions the surfactants are concentrated and aggregated inside the gel phase; simultaneously, the gel collapses. [21][22][23][24][25] The practical aspects of the present research are connected with the design of new materials based on hydrogels possessing the combination of properties of the gel and feature dye.…”
Section: Introductionmentioning
confidence: 99%